2001
DOI: 10.1029/2000gl012535
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh lidar observations of mesospheric inversion layers at Poker Flat, Alaska (65 °N, 147°W)

Abstract: Abstract. Rayleigh lidar measurements of the stratosphere and mesosphere have been made on an ongoing basis over a threeyear period at Poker Flat, Alaska (65 ø N, 147 ø W). These observations have yielded 27 nightly measurements of the middle atmosphere temperature profile (-40-80 km). These nighttime measurements are distributed between August and April. Mesospheric inversion layers have been observed on five occasions. The average altitude of the inversion layer peak is 60 km, with average amplitude of 1õ K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 28 publications
0
41
1
Order By: Relevance
“…Both these scenarios are discussed in detail e.g., in the review article by Meriwether and Gerrard (2004). The adiabatic temperature gradient above both inversion layers detected in our case has been repeatedly observed by lidars (e.g., Whiteway et al, 1995;Thomas et al, 1996;Cutler et al, 2001;Duck and Greene, 2004;Liu et al, 2004;Collins et al, 2011) and has most often been the only argument regarding turbulence activity associated with temperature inversions. However, Thomas et al (1996) performed simultaneous observations of MILs with Rayleigh lidar and mesospheric echoes with VHF radar and concluded that both dynamic and convective instabilities (and, therefore, the generated turbulence) are associated with these phenomena.…”
Section: Discussionmentioning
confidence: 86%
“…Both these scenarios are discussed in detail e.g., in the review article by Meriwether and Gerrard (2004). The adiabatic temperature gradient above both inversion layers detected in our case has been repeatedly observed by lidars (e.g., Whiteway et al, 1995;Thomas et al, 1996;Cutler et al, 2001;Duck and Greene, 2004;Liu et al, 2004;Collins et al, 2011) and has most often been the only argument regarding turbulence activity associated with temperature inversions. However, Thomas et al (1996) performed simultaneous observations of MILs with Rayleigh lidar and mesospheric echoes with VHF radar and concluded that both dynamic and convective instabilities (and, therefore, the generated turbulence) are associated with these phenomena.…”
Section: Discussionmentioning
confidence: 86%
“…They pointed out that broad spectra measured with the Indian MST Radar located in Gadanki are associated with so-called lower MILs observed by the co-located Rayleigh lidar and that both are related to strong turbulence activity at those heights. Lidar observations at mid-latitudes by Whiteway et al (1995); Thomas et al (1996); Liu et al (2004) and high-latitudes by Cutler et al (2001); Duck and Greene (2004); Collins et al (2011) have shown that MILs are often associated with turbulence activity which is reflected in the lidar temperature measurements as an adiabatic lapse rate on top of the inversion layers. On the other hand, numerical simulations by Liu et al (2000) showed that vigorous turbulence is required to change the thermal structure to the shape associated with temperature inversions.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that this procedure has been applied in many previous studies investigating the phenomenon of mesospheric inversion (Leblanc et al, 1998;Meriwether and Gardner, 2000;Duck et al, 2001;Duck and Greene, 2004;Cutler et al, 2001;Siva Kumar et al, 2001;Ratnam et al, 2003;Gan et al, 2012). Figure 1 shows an example of a vertical temperature profile obtained from lidar and SABER observations over the Réunion site and showing a significant MIL structure.…”
Section: Detection and Analysis Of The Mils (Methodology)mentioning
confidence: 99%